Data Derivation Investigation - Kadam, S.S.; Kumbharkar, P.B. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Malicious software is a major issue in today’s computer world. Such software can silently reside in user’s computer and can easily interact with computing resources. It is necessary to improve the honesty of host and its system data. For improvement in security and honesty of host, this work is introduced. This mechanism ensures the correct origin or provenance of critical system information and prevents utilization of host resources by malware. Using this mechanism the source where a piece of data is generated can be identified. A cryptographic origin approach ensures system properties and system- data integrity at kernel level. A frame work is used for restricting outbound malware traffic. This frame work identifies network activities of malware. This frame work can be used as powerful personal firewall for investigating outgoing traffic of a host. Specifically, our derivation verification scheme requires outgoing network packets to flow through a checkpoint on a host, to obtain proper origin proofs for later verification.